Preparation of Flower-like Nickel-Based Bimetallic Organic Framework Electrodes for High-Efficiency Hybrid Supercapacitors - Di Jiang (MDPI AG, 2021)
Metal organic frameworks (MOFs) have been rapidly developed in the application of electrode materials due to their controllable morphology and ultra-high porosity. In this research, flower-like layered nickel-based bimetallic MOFs microspheres with different metal central ions were synthesized by solvothermal method. Compared with Ni-MOFs, the optimization of the specific capacitance of NiCo-MOFs and NiMn-MOFs was been confirmed. For example, the specific capacitance of NiCo-MOFs can reach 882 F·g−1 at 0.5 A·g−1 while maintaining satisfactory cycle life (the specific capacity remains 90.1% of the initial value after 3000 charge-discharge cycles at 5 A·g−1). In addition, the NiCo-MOFs//AC HSCs, which are composed of NiCo-MOFs and activated carbon (AC), achieved a maximum energy density of 18.33 Wh·kg−1 at a power density of 400 W·kg−1, and showed satisfactory cycle life (82.4% after 3000 cycles). These outstanding electrochemical properties can be ascribed to the synergistic effect between metal ions, the optimized conductivity, and the unique layered stacked flower structure, which provides a smooth transmission channel for electrons/ions. In addition, this research gives a general method for the application of MOFs in the field of supercapacitors.